Racing Dobbs - Franke, Katherine; Mar, Ria Tabacco (Columbia Journal of Gender and Law, 2024)
In Dobbs v. Jackson Women’s Health Organization, the U.S. Supreme Court reversed Roe v. Wade’s limits on a state’s ability to restrict, and indeed completely outlaw, abortion. The case raises fundamentally important questions about rights to reproductive autonomy, bodily integrity, sex equality, privacy, and health.